Isolation, structure, and functional elucidation of a modified pentapeptide, cysteine protease inhibitor (CPI-2081) from streptomyces species 2081 that exhibit inhibitory effect on cancer cell migration - Singh, Jay Prakash; Tamang, Sudarsan; Rajamohanan, P. R.; Jima, N. C.; Chakraborty, Goutam; Kundu, Gopal C.; Gaikwad, Sushama M.; Khan, Mohammad Islam (Journal of Medicinal Chemistry, 2010)
Cysteine proteases play an important role in cell migration and tumor metastasis. Therefore, their inhibitors are of colossal interest, having potential to be developed as effective antimetastatic drugs for tumor chemotherapy. Traditionally, secondary metabolites from streptomyces show a wide range of diversity with respect to their biological activity and chemical nature. In this article, we have described the characterization of small molecule cysteine protease inhibitor, CPI-2081 (compound 1), a mixture of two novel pentapeptides, compound 1a (736.71 Da), and compound 1b (842.78 Da), isolated from Streptomyces species NCIM2081, following solvent extraction and repeated HPLC based on C18 chemistry, and completely characterized using a variety of both ID and 2D NMR spectroscopy. Further, it was found that nanomolar concentration of compound 1 is able to inhibit papain hydrolytic activity. Also, compound 1 significantly inhibits tumor cell migration at sub cytotoxic concentration, indicating its remarkable potential to be developed as antimetastatic drug, which will make chemotherapy more localized and specific, thereby minimizing the hazardous side effects on normal tissues.

Biological synthesis of silver nanoparticles using the fungus humicola sp and evaluation of their cytoxicity using normal and cancer cell lines - Syed, Asad; Saraswati, Supriya; Kundu, Gopal C.; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
Nanoscience is a new born science of the modern era and taps into the potential of particles at nanoscale. Bulk materials reduced to nanoscale dimensions thus obtain unique properties such as electronic, optical, magnetic and chemical. As far as synthesis of nanoparticles is concerned, biological synthesis has recently sparked a great interest as compared to other available chemical and physical methods on account of its eco-friendliness and cost-effectiveness. Here we report, for the first time, the biosynthesis of silver nanoparticles by the thermophilic fungus Humicola sp. The fungus when reacted with Ag+ ions reduces the precursor solution and leads to the formation of extracellular nanoparticles as monitored by ultra violet visible spectroscopy (UV-Vis). The morphology of nanoparticles is found to be spherical with good dispersity as revealed by transmission electron microscopy (TEM). Cell viability assays were carried out to assess the cytotoxicity of silver nanoparticles on NIH3T3 mouse embryonic fibroblast cell line and MDA-MB-231 human breast carcinoma cell line. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Fungus; Humicola sp.; Nanoparticles; Silver

One-pot fluorescent labeling protocol for complex hydroxylated bioactive natural products - Haldar, Saikat; Kumar, Santosh; Kolet, Swati P.; Patil, Harshal S.; Kumar, Dhiraj; Kundu, Gopal C.; Thulasiram, Hirekodathakallu V. (Journal of Organic Chemistry, 2013)
Tagging of small bioactive molecules with a fluorophore is a highly sensitive method to trace their cellular activities through real-time visual information. Here we disclose a 7-nitrobenzo-2-oxa-1,3-diazole (NBD)-based, high-yielding, one-pot labeling protocol for hydroxylated molecules using Yamaguchi coupling as the key reaction. This methodology was successfully applied on several sensitive and complex hydroxylated bioactive compounds including 7-deacetylazadiradione, simvastatin, camptothecin, andrographolide, cinchonine, beta-dihydroartemisinin, and azadirachtin A. Further, utility of this protocol was illustrated on the cytotoxic activity of azadiradione derivatives against several cancer cell lines through cell imaging of two qualified fluorescent probes.

Notch1-MAPK signaling axis regulates CD133+ cancer stem cell-mediated melanoma growth and angiogenesis - Kumar, Dhiraj; Kumar, Santosh; Gorain, Mahadeo; Tomar, Deepti; Patil, Harshal S.; Radharani, Nalukurthi N. V.; Kumar, Totakura V. S.; Patil, Tushar V.; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (Journal of Investigative Dermatology, 2016)
Functional characterization and understanding of the intricate signaling mechanisms in stem-like cells is crucial for the development of effective therapies in melanoma. We have studied whether melanoma cells are phenotypically distinct and hierarchically organized according to their tumorigenic nature. We report that melanoma-specific CD133(+) cancer stem cells exhibit increased tumor-initiating potential, tumor-endothelial cell interaction, and lung metastasis. These cells are able to transdifferentiate into an endothelial-like phenotype when cultured under endothelial differentiation-promoting conditions. Mechanistically, Notch1 upregulates mitogen-activated protein kinase activation through CD133, which ultimately controls vascular endothelial growth factor and matrix metalloproteinase expression in CD133(+) stem cells leading to melanoma growth, angiogenesis, and lung metastasis. Blockade or genetic ablation of Notch1 and mitogen-activated protein kinase pathways abolishes melanoma cell migration and angiogenesis. Chromatin immunoprecipitation and reporter assays revealed that Notch1 intracellular domain regulates CD133 expression at the transcriptional level. Andrographolide inhibits Notch1 intracellular domain expression, Notch1 intracellular domaindependent CD133-mediated mitogen-activated protein kinase and activator protein-1 activation, and epithelial to mesenchymal-specific gene expression, ultimately attenuating melanoma growth and lung metastasis. Human malignant melanoma specimen analyses revealed a strong correlation between Notch1 intracellular domain, CD133, and p-p38 mitogen-activated protein kinase expression and malignant melanoma progression. Thus, targeting Notch1 and its regulated signaling network may have potential therapeutic implications for the management of cancer stem cell-mediated melanoma progression.

Epoxyazadiradione suppresses breast tumor growth through mitochondrial depolarization and caspase-dependent apoptosis by targeting PI3K/Akt pathway - Kumar, Dhiraj; Haldar, Saikat; Gorain, Mahadeo; Kumar, Santosh; Mulani, Fayaj A.; Yadav, Amit S.; Miele, Lucio; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (BMC Cancer, 2018)
Background: Breast cancer is one of the most commonly diagnosed invasive cancers among women around the world. Among several subtypes, triple negative breast cancer (TNBC) is highly aggressive and chemoresistant. Treatment of TNBC patients has been challenging due to heterogeneity and devoid of well-defined molecular targets. Thus, identification of novel effective and selective agents against TNBC is essential. Methods: We used epoxyazadiradione to assess the cell viability, mitochondrial potential, ROS level, cell migration, apoptosis and protein expression in cell culture models of TNBC MDA-MB-231 and ER+MCF-7 breast cancer cells. The molecular mechanism was examined in two different type of breast cancer cells in response to epoxyazadiradione. We have also analyzed the effect of epoxyazadiradione on breast tumor growth using in vivo mice model. Results: In this study, we for the first time investigated that out of 10 major limonoids isolated from Azadirachta indica, epoxyazadiradione exhibits most potent anti-cancer activity in both TNBC and ER+breast cancer cells. Epoxyazadiradione induces apoptosis and inhibits PI3K/Akt-mediated mitochondrial potential, cell viability, migration and angiogenesis. It also inhibits the expression of pro-angiogenic and pro-metastatic genes such as Cox2, OPN, VEGF and MMP-9 in these cells. Furthermore, epoxyazadiradione attenuates PI3K/Akt- mediated AP-1 activation. Our in vivo data revealed that epoxyazadiradione suppresses breast tumor growth and angiogenesis in orthotopic NOD/SCID mice model. Conclusion: Our findings demonstrate that epoxyazadiradione inhibits PI3K/Akt-dependent mitochondrial depolarisation, induces apoptosis and attenuates cell migration, angiogenesis and breast tumor growth suggesting that this compound may act as a potent therapeutic agent for the management of breast cancer.
Keywords: Angiogenesis; Apoptosis; Breast cancer; Limonoids; Metastasis; PI3K

Graphene oxide supported liposomes as red emissive theranostics for phototriggered tissue visualization and tumor regression - Prasad, Rajendra; Yadav, Amit S.; Gorain, Mahadeo; Chauhan, Deepak S.; Kundu, Gopal C.; Srivastava, Rohit; Selvaraj, Kaliaperumal (ACS Applied Bio Materials, 2019)
Selective tissue visualization and localized tumor regression without affecting the surrounding healthy tissues are critical concerns in cancer nanomedicine. Importantly, the complete wrapping of a flimsy matrix like liposome by multifunctional graphene oxide is an interesting engineering idea for nanomedicine design. Moreover, designing a safe and biodegradable nanohybrid with significant theranostic ability is a current need for targeted combined therapies. Here, we report a comprehensive result of in vivo tumor diagnosis and phototriggered tumor regression using a biodegradable red emissive nanotheranostic system, viz., graphene oxide flakes fortified liposome (GOF-Lipo), functionalized with folic acid (FA): GOF-Lipo-FA. Graphene oxide support enhances the stability of drug-loaded liposomes in an extracellular environment that prevents the premature release of loaded anticancer drug from the liposomal cavity. Promising outcomes of tumor regression (∼300 to 25 mm3) from organized cellular and animal studies are demonstrated in this work. These studies reveal superior biocompatibility, deep intracellular localization, 4T1 breast tumor diagnosis, and long time tumor binding ability of an injected emissive nanohybrid. Overall, a single dose of designed multifunctional systems demonstrates the best tumor regression.

Engineered PLGA core-lipid shell hybrid nanocarriers improve the efficacy and safety of irinotecan to combat colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS BIOMATERIALS SCIENCE & ENGINEERING, 2024)
Keywords: BULK-POLYMERIZATION; Drug-delivery; LIPOSOMAL DOXORUBICIN

Poly(d,l-lactide-co-glycolide) surface-anchored biotin-loaded irinotecan nanoparticles for active targeting of colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS Omega, 2024)
A poly-(d,l-lactide-co-glycolide) (PLGA) copolymer was synthesized using the ring-opening polymerization of d,l-lactide and glycolide monomers in the presence of zinc proline complex in bulk through the green route and was well characterized using attenuated total reflectance-Fourier transform infrared, H-1 and C-13 nuclear magnetic resonance, gel permeation chromatography, differential scanning calorimetry, X-ray diffraction, matrix-assisted laser desorption/ionization time-of-flight, etc. Furthermore, PLGA-conjugated biotin (PLGA-B) was synthesized using the synthesized PLGA and was employed to fabricate nanoparticles for irinotecan (Ir) delivery. These nanoparticles (PLGA-NP-Ir and PLGA-B-NP-Ir) were tested for physicochemical and biological characteristics. PLGA-B-NP-Ir exhibited a stronger cellular uptake and anticancer activity as compared to PLGA-NP-Ir in CT-26 cancer cells (log p < 0.05). The accumulation and retention of fluorescence-labeled nanoparticles were observed to be better in CT-26-inoculated solid tumors in Balb/c mice. The PLGA-B-NP-Ir-treated group inhibited tumor growth significantly more (log p < 0.001) than the untreated control, PLGA-NP-Ir, and Ir-treated groups. Furthermore, no body weight loss, hematological, and blood biochemical tests demonstrated the nanocarriers' nontoxic nature. This work presents the use of safe PLGA and the demonstration of a proof-of-concept of biotin surface attached PLGA nanoparticle-mediated active targeted Ir administration to combat colon cancer. To treat colon cancer, PLGA-B-NP-Ir performed better due to specific active tumor targeting and greater cellular uptake due to biotin.